Views and Visions : Contemporary Art from Tampere. - Design Works Foundation, Gateshead; Tampere Art Museum, Tampere (Tampere : Tampere Art Museum, 1993)
Mäkilä, Irmeli ; Saukkonen, Teemu ; Lehtinen, Tuula ; Väätti, Ilkka ; Jämsä, Aarne ; Juvonen, Osmo ; Kivinen, Markku ; Siukonen, Jyrki ; Hirvonen, Jouni ; Varrela, Vesa ; Lehtonen, Henrietta ; Rauhala, Osmo ; etc.
Views and Visions : Contemporary Art from Tampere, Design Works Foundation, Gateshead, 8 January - 19 February 1993 / Tampere Art Museum, 20 March - 2 May 1993
boek